AGEMARA: MEDIUM TO ENHANCE EARLY READING LITERACY IN INDONESIAN LANGUAGE LEARNING (FEASIBILITY AND PRACTICALITY STUDY) - Setiawaty, Rani; Sholekhah, Putri Imatriyani; Ardianti, Sekar Dwi; Elle, Jude Cris Alonso T. (STKIP Pesisir Selatan, 2025)
Objective: This study aims to develop and test the feasibility and practicality of AGEMARA (Jepara Local Wisdom-Based Beginning Reading Application) as an innovative digital learning media to improve the beginning reading literacy skills of second-grade elementary school students. Methods: The research used the Research and Development (R&D) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Material, media, and language experts conducted feasibility testing, while practicality testing was obtained through teacher and student responses to the application's use. Results: Validation results showed that media experts at 69.3%, material experts at 80.4%, and language experts at 79.95% deemed AGEMARA feasible based on assessments. Meanwhile, the results of the practicality test showed a very practical category, with a score of 87.3% from teachers and 96.1% from students. The application was deemed attractive, easy to use, and relevant to the local cultural context of Jepara. Novelty: AGEMARA offers innovation in the form of integrating Jepara's local wisdom—including carvings, wayang krucil, and coastal traditions—into Android-based early reading lessons. This integration makes learning contextual and meaningful, and supports the strengthening of character and cultural literacy in elementary school students.